High anticancer efficacy of solid lipid nanoparticles containing Zataria multiflora essential oil against breast cancer and melanoma cell lines - Alireza Valizadeh; Ali Asghar Khaleghi; Ghazaal Roozitalab; Mahmoud Osanloo (BMC, 2021)
Abstract Background The cancer burden is rising rapidly worldwide, and it annually causes about 8.8 million deaths worldwide. Due to chemical drugs' side effects and the emergence of resistance, the development of new green drugs has received much attention. We aimed to investigate whether solid-lipid nanoparticles containing essential oil of Zataria multiflora (ZMSLN) enhanced the anticancer efficacy of the essential oil against breast cancer (MDA-MB-468) and melanoma (A-375) cells. Results ZMSLN was prepared by the high-pressure homogenizer method; particle size 176 ± 8 nm, polydispersity index 0.22 ± 0.1, entrapment efficiency 67 ± 5%. The essential oil showed a dose-dependent antiproliferative effect on MDA-MB-468 and A-375 cells at all examined concentrations (75, 150, 300, 600, and 1200 μg/mL). Interestingly, after treating both cells with 75 μg/mL of ZMSLN, their viabilities were reduced to under 13%. Conclusion The finding showed that ZMSLN had a distinct antiproliferative efficacy; it could thus be considered a green anticancer candidate for further in vivo and in vivo studies.